A Retrospective Analysis of the Correlation between Functional Imaging and Clinical Outcomes in Grade 3 Neuroendocrine Tumors (NETs G3) - Alice Laffi; Marzia Colandrea; Giuseppe Buonsanti; Samuele Frassoni; Vincenzo Bagnardi; Francesca Spada; Eleonora Pisa; Massimo Barberis; Manila Rubino; Chiara Maria Grana; Francesco Ceci; Nicola Fazio (Diagnostics, 2021)
Grade 3 (G3) neuroendocrine tumors (NETs) are a novel category among digestive neuroendocrine neoplasms, characterized by Ki-67 >20% and a well-differentiated morphology, presenting high intra-tumor heterogeneity. We aimed to explore the role of dual-tracer PET imaging (68Gallium (Ga)-DOTATOC and 18Fluorodeoxyglucose (FDG)) as overall survival (OS) predictor in NET G3 patients. We performed a retrospective analysis in NET G3 patients treated at our institution between 2003 and 2021. Accordingly, 30 NET G3 patients were analyzed. 68Ga-DOTA-TOC and 18F-FDG uptake were assessed by tumor/non-tumor (T-nonT) ratio. We reported a slightly better OS for patients with ≥75% concordance between 68Ga-DOTA-TOC and 18F-FDG PET/CT (p = 0.42). Among patients with discordant functional imaging, we reported a better 5-y OS rate for patients with a prevalent 68Ga-DOTATOC vs. 18F-FDG PET/CT (p = 0.016). In positive 18F-FDG PET/CT cases, we reported a better OS for <4 vs. ≥4 T/non-T ratio (p = 0.021). Among upfront-NET G3 patients with concordant exams, 5-y OS rate was 83.3% (95% CI: 27.3–97.5). Among patients with discordant exams, 5-y OS rate was 81.3% (52.5–93.5), 100% for those with prevalent receptor expression, and 50% (11.1–80.4) for those with prevalent 18F-FDG uptake. Our findings suggest that dual-tracer PET/CT can be considered as a predictor of patient outcome, able to stratify NET G3 patients with poorer prognosis.